The perceived impact of digital video piracy on the growth of Over-The-Top services in South Africa - Knowles, Sharon (University of the Witwatersrand, Johannesburg, 2021)
Digital video content piracy, like tv-series, movies and sporting content is a growing trend in South Africa. This dissertation aims to understand that impact that digital video content piracy has on streaming service subscriptions and the impact on these service providers, thus further contributing to the research on digital piracy. The key questions examined in the dissertation aimed to answer whether the increased availability of digital video content has an impact on digital piracy and whether the increase in piracy is driven by OTT services in South Africa. The dissertation thus examines the literature around digital piracy, anti-piracy tools and deployment, consumption , growth habits of Over-the-top (OTT) services in South Africa as well as content distribution. A quantitative research approach is used to collect original data through a structured survey containing a combination of Likert scale and close-ended questions. The research demonstrates that piracy is driven by digital video content availability and that OTT service providers provide significant input into the efforts regarding utilising anti-piracy tools to stop piracy. The availability of digital video content can be therefore manipulated and adjusted to suit the entertainment industry and can halt revenue loss through piracy
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Digital Piracy; OTT services; Torrenting; UCTD; SDG-8: Decent work and economic growth